Differences in the interaction between CETP Taq1B polymorphism and dietary fat intake on lipid profile of normolipedemic and dyslipidemic patients with type 2 diabetes mellitus. Issue 1 (February 2018) - Kalantar, Zahra; Eshraghian, Mohamad Reza; Sotoudeh, Gity; Djalali, Mahmoud; Mansouri, Anahita; Alvandi, Ehsan; Javadi, Fatemeh; Mahmoudi, Maryam; Koohdani, Fariba
Summary: Background & aim: Dyslipidemia is one of the major complications in patients with type 2 diabetes mellitus (T2DM). Dietary fat intake and genetic factors including CETP Taq1B polymorphism could also affect lipid profile concentrations, in particular HDL-c. We decided to study the frequency of this polymorphism and its interaction with dietary fat intake on HDL-c concentration among Iranian T2DM patients with and without dyslipidemia. Methods: In this comparative study, serum samples were collected from 55 patients with dyslipidemia and 129 patients without dyslipidemia. Validated semi-quantitative FFQ was used for food consumption data. CETP Taq1B polymorphism was studied by polymerase chain reaction-restriction length polymorphism (PCR-RFLP). We used χ 2 and two-way ANOVA tests for statistical analysis. Results: The frequency of B1B1 genotype was higher in patients with dyslipidemia (p = 0.01). There was no significant relationship between CETP Taq1B polymorphism and lipid profile concentrations. In patients without dyslipidemia, the interaction between the polymorphism and total fat intake on HDL-c concentration as well as TG/HDL ratio was significant (p = 0.02 and p = 0.009 respectively). This was more evident in B1B1 genotype. Moreover, HDL-c concentration was significantly higher in B2B2 genotype with low total fat intake. Conclusion: Higher total fat intake may affect the relationship between CETP Taq1B polymorphism and HDL-c concentration in patients with normolipidemic T2DM.